1973
DOI: 10.1182/blood.v41.1.17.17
|View full text |Cite
|
Sign up to set email alerts
|

Sideroblastic Anemia in Multiple Myeloma: A Preleukemic Change

Abstract: In a 10-yr observation period, 75 patients with multiple myeloma have been studied, and 55 of these were treated daily with low dose melphalan by mouth. Of these, four developed sideroblastic anemia, manifested by anemia, thrombocytopenia, aniso-poikilocytosis, and hypochromic stippled cells in the blood, and ringed sideroblasts in the bone marrow. In two patients, this complication occurred after more than 7 yr of therapy and at a time when there was no evidence of myeloma. In a third patient, it occurred whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1974
1974
1982
1982

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…All patients had some form of cytopenia more than four months before leukemic transformation was observed. These changes during the preleukemic period correspond very well with descriptions given by other authors (9,13). The types of leukemia developing in our patients have been observed before in myeloma patients (16).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…All patients had some form of cytopenia more than four months before leukemic transformation was observed. These changes during the preleukemic period correspond very well with descriptions given by other authors (9,13). The types of leukemia developing in our patients have been observed before in myeloma patients (16).…”
Section: Discussionsupporting
confidence: 93%
“…The occurrence of acute leukemia in myeloma patients has been discussed in several reports (3,7,11,13,16). It has been found that myeloma patients treated with alkylating agents run a greater risk of developing leukemia than those not treated with these agents (3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of acute leukaemia, lymphosarcomas or erythroleukaemias has been reported among patients who received chlorambucil for a long time (Osterberg & Randing 1970, Laroche et al 1972, Catovsky & Galton 1972, Zittoun et al 1972. Some sideroblastic anaemias have preceded for several months an acute myeloblastic leukaemia in patients with multiple myeloma treated by melphalan (Khaleeli et al 1973). There has also been established the relative frequency of acute leukaemia among patients with Hodgkin's disease treated by irradiation or prolonged chemotherapy with chlorambucil (Jacquillat et al 1973).…”
Section: -73mentioning
confidence: 99%